Mediating effects of teachers’ organisational commitment on relationship between instructional leadership, self-efficacy and primary school students' academic performance in Pakistan - Khan, Adeel Ahmed (2021)
The need for Pakistani students to achieve a high rating in the assessment standards has created pressure on the nation and demand schools and their principals to improve students' academic performances. Many researchers have identified demographic, socioeconomic status, family and school factors that contributing to students' academic performances. Schools can improve their learning outcomes regardless of initial achievement levels by changing critical organizational aspects such as teachers' organizational commitment, instructional leadership and teachers' self-efficacy. The study aimed to determine the mediation effect of teachers' organizational commitment on the relationship between instructional leadership, self-efficacy and primary school students' academic performance in Pakistan. It was a descriptive correlational study using a survey method. Multistage probability sampling was used with questionnaires as research instruments. A total of 501 questionnaires were distributed with the response rate was 88%, and 440 responses were received. The reliability and validity of the research questionnaires were determined using coefficient alpha and composite reliability with alpha value are 0.830, 0.906 and 0.928 for all three instruments. The statistical procedures used to analyze the data included descriptive, Structural Equation Modelling (SEM) and mediation analysis The hypothesized model exhibits a good model fit to the data. The findings showed that principal instructional leadership effect on the students' academic performance was statistically not significant with β value is -.005 and p-value is -0.931. Furthermore, teachers' self-efficacy and teachers' organizational commitment were predictors to students' academic performance (β= .633, p = 0.000) and (β= .210, p = 0.008) respectively. The mediation analysis results revealed that principal instructional leadership had an indirect effect on students' academic performance through teachers' organizational commitment with the standardized indirect effect of 0.058 and the P-value of 0.042, and the degree of mediation was full mediation. Based on the study's findings, it was concluded that the influence of the selected factors identified in this study for the primary schools' students' academic performance and needed to be addressed for successful educational practice. The findings of this research study have implications for regulating policies and practices that would have a constructive impact on instructional leadership, teachers' self-efficacy, teachers' organizational commitment and students' academic performance. In addition, the findings of this study have provided evidence base information that may assist practitioners and administrators to develop and manage policy directions to improve Pakistani students' academic performance. The current study's findings contributed to the empirical literature that teacher organizational commitment is a valid mediator between instructional leadership and students' academic performance. The study recommends that instructional leadership, teachers' organizational commitment, and self-efficacy aspects are to be included in training programs to address the problem of students' academic performance in Pakistan.